Assessment of Hematological Parameters and Immune Cell CD Markers in Iraqi patients with Acute Myeloid Leukemia - M. Jaleel, Karar; H. Allami, Risala; W. Issa, Yasir (Al-Nahrain Journal of Science, 2025)
Acute Myeloid Leukemia (AML) is a heterogeneous hematologic malignancy characterized by varying genetic and immunophenotypic profiles. This study includes 120 participants classified into 40 healthy subjects, 40 newly diagnosed AML, and 40 treated AML patients analyzed demographic characteristics, hematological parameters, and immunological biomarkers in newly diagnosed and treated AML patients in a Baghdad teaching hospital, Baghdad, Iraq. From the period of December 2023 and March 2024. The results revealed statistically significant differences (P value 0.05). The study underscores the significance of regular assessment of parameters for effective diagnosis and treatment, highlighting the potential of CD33 and CD13 as therapeutic targets in AML.